A Pilot Randomized Trial of a Brief Mental Health Crisis Prevention Program for Autistic Youth. - Kalb, Luther G.; Perrin, Jeremy; Sollins, Elie; Horton, Jennifer; Cross, Elizabeth A.; Vasa, Roma A. (Journal of Autism & Developmental Disorders, 2026)
Autistic youth are at significant risk of experiencing a mental health crisis. Unfortunately, most clinical approaches to crisis management, such as referral to the emergency department, can be traumatic. At present, no crisis prevention programs have been developed for or rigorously tested among autistic youth. The goals of this study were to develop a parent-mediated mental health crisis prevention program, delivered virtually by a licensed clinician over three 1-h sessions, and test its efficacy via a randomized controlled trial. The trial included 49 autistic youth, ages 3 to 12 years, and their parents, who were recruited from an outpatient autism center. All children had behavioral concerns but were not at acute risk of crisis. Parents in the crisis prevention program (n = 25) reported that the strategies were safe and feasible; they were also very satisfied with the program. Compared to active controls (n = 24), who received the Autism Speaks Challenging Behavior Toolkit, the crisis prevention program was found to have greater improvements in caregiver-reported knowledge, confidence, and preparedness regarding management of crisis behaviors (p <.05). However, effects on caregiver-reported child irritability and behavioral acuity did not differ (p >.05). The brief crisis prevention program is safe, feasible, and acceptable to parents. While it improves mental health crisis preparedness, further research on its efficacy in reducing crisis risk is needed.